Effect of different warm-up strategies on countermovement jump and sprint performance in basketball players - de Sousa Fortes, L.; Paes, P. P.; Mortatti, A. L.; Perez, A. J.; Cyrino, E. S.; de Lima-Júnior, D. R. A. A.; Moreira, A. (Isokinetics and Exercise Science, 2018)
BACKGROUND: Despite the importance of knowledge regarding the effects of different warm-up strategies not much is known about these effects and specific strategies with respect to basketball players. OBJECTIVE: To analyze the effect of different warm-up strategies on two specific functional actions of basketball, countermovement jump and speed. METHODS: Nineteen male basketball players aged between 19 and 27 (23.7 ± 1.1 years) were recruited. Experimental sessions were conducted with a 24 h interval in-between. The athletes performed randomly the five warm-up conditions (aerobic + resistance training, aerobic + jumps, resistance training + jumps, jumps only, and control condition) followed by the physical tests (countermovement jump and a 20-m sprint). RESULTS: All warm-up conditions increased significantly the countermovement jump and sprint performance mainly for the jumps only condition for countermovement jump performance (p = 0.01) and resistance training + jumps for sprint performance (p = 0.01). CONCLUSION: Warm-up with jumps was the most effective method for increasing countermovement jump while resistance training + jumps was the best strategy to enhance 20 m speed performance.